The relationship between administrative academic staff’s leadership styles and their level of emotional intelligence : a case study in UiTM Sarawak / Sueb Ibrahim - Ibrahim, Sueb (2017)
As the context of leadership is changing, to lead effectively will be critical to the longterm success of organizations. Therefore, academic leaders at higher education institutions need to combine several leadership qualities in order to succeed. Academic leaders have to develop their rational in establishing which leadership style will result to high performance outcomes and leadership effectiveness. Thus, the nature of the leader’s emotional connectedness to others is apparently in the growing interest in numerous studies on the effect of emotional intelligence on leadership. Moreover, at present, there seems to be increasingly attention being given to organizational life and leadership and general agreement about the need to incorporate the role of emotion into research on academic leaders at higher education institutions.